Rice Straw: A Waste with a Remarkable Green Energy Potential - Maurizio Bressan; Elena Campagnoli; Carlo Giovanni Ferro; Valter Giaretto (Energies, 2022)
With reference to the province of Novara in northwest Italy, this study aims to raise awareness about the environmental benefits that can derive from the use of alternative rice straw management practices to those currently in use, also highlighting how the use of these straws for energy purposes can be a valid alternative to the use of non-renewable resources. Using the LCA (Life Cycle Assessment) method, the two rice straw management practices currently in place (open field combustion and straw incorporation) were compared with an alternative strategy consisting in their collection and removal. The results show that removal of straw allows reducing the emissions of pollutants significantly: about one-hundredth of the PM (Particulate Matter) formation compared to the open-field burning and about one-tenth of the ozone depletion (CFCs, HCFCs, halons, etc.) compared to both the other two practices. Moreover, the LCA results show how the use of rice straw to produce energy as an alternative to conventional fuels helps to reduce the global warming potential of rice cultivation.